Effect of modulation technique in Mach-Zehnder Modulator (MZM) in optical OFDM system - Muhammad Towfiqur, Rahman; Abdullah, Khaizuran; Islam, Md Rafiqul (IRACST, 2014)
This paper highlights the bit error rate (BER) performance of a radio-over-fiber system utilizing binary phase shift keying (BPSK), M-QAM, QPSK in the external modulator which is the Mach-Zehnder modulator (MZM). The results have been obtained from the RoF link over 8, 30, 60 90 and 120 km distance to study the effect of nonlinear dispersion and attenuation of signal and compare the results other modulation. Furthermore, the chromatic dispersion has no effect on MZM whereas it has distinct effect on OOK modulation scheme without optical dispersion compensation, the performances of different modulation schemes such as OOK, PPM and PAM are analyzed. Comparisons of transmission distance, transmission capacity, bandwidth efficiency in coherent optical orthogonal frequency division multiplexing (CO-OFDM) system are included. Simulation results are given using Matlab, Simulink and Optisystem software. The results also show the importance of upconverter to reduce the nonlinearity effect in the transmission channel.